(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Clean air is one of the basic requirements of human health. However, during the process of economic development, pollution is found to be a significant health hazard worldwide. Pollution is the introduction of harmful materials into the environment, which causes diseases and premature death. One of the major causative materials for pollution is pollutants. A pollutant is a substance introduced into the environment that has undesired effects. Among the different kinds of pollutants, air pollutants are easily spreadable. Air pollutants refer to naturally occurring substances, such as particulate matter, ozone, sulfur oxide, nitrogen oxides, phthalate, and volatile organic compounds. Household combustion devices, motor vehicles, burning of fossil fuels, industrial facilities, and forest fires are common sources of air pollutants. Thus, these air pollutant substances affect the health of children and women. Also, Air pollutants cause mortality as well as specific diseases, such as stroke, ischaemic heart disease, chronic obstructive pulmonary disease, and pneumonia in women and children. Therefore, the current review paper’s objective is to explain air pollutants, such as sulfur and nitrogen oxides, particulate matter, and phthalate along with their health effects. Also, this review explains the air pollutants, their types, and their health effects on women and children.